2005
DOI: 10.1111/j.1601-5223.2004.01865.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of SSRs for predicting the hybrid yield and yield heterosis in 15 key inbred lines of Chinese maize

Abstract: A challenge to maize breeders is to predict and identify inbred lines that can produce highly heterotic hybrids precisely. In the present study we surveyed the genetic diversity among 15 elite inbred lines of maize in China with SSR markers and assessed the relationship between SSR marker and hybrid yield/yield heterosis in a diallel set of 105 crosses. Forty-three SSR primers selected from all sixty-three primers gave stable profiles amplified in the sample of 15 inbred lines, which could clearly resolve on 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 26 publications
3
13
1
2
Order By: Relevance
“…Many key genes governing these traits have also been cloned and identified. At the same time, the genetic diversity and division of heterotic groups of maize inbred lines have been studied intensively (Taramino and Tingey 1996;Xu et al 2004;Menkir et al 2005;Legesse et al 2007). Patterns of genetic transmission of these QTLs and key genes, however, remain largely unknown in key inbred lines of maize and their derived lines.…”
Section: Introductionmentioning
confidence: 99%
“…Many key genes governing these traits have also been cloned and identified. At the same time, the genetic diversity and division of heterotic groups of maize inbred lines have been studied intensively (Taramino and Tingey 1996;Xu et al 2004;Menkir et al 2005;Legesse et al 2007). Patterns of genetic transmission of these QTLs and key genes, however, remain largely unknown in key inbred lines of maize and their derived lines.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found SSR as a good complementing tool along with morphological markers for maize genetic characterization. low level of polymorphism are some of the major limitations of the biochemical markers (Xu et al, 2004). Lopes et al, (2015) investigated the genetic diversity of twenty-two sweet corn cultivars viz., seventeen open-pollinated varieties (OPV) and five hybrids (H) by applying 30 polymorphic simple sequence repeat markers.…”
Section: Introductionmentioning
confidence: 99%
“…Betran et al (2003) andMladenović Drinić et al (2012) found positive correlation between genetic distance of inbred lines and resulting heterosis, but some studies showed weak or no correlation (Xu et al, 2004;Kiula et al, 2007).…”
Section: Plus-hybrid Effect On Grain Yieldmentioning
confidence: 99%